Progress in bioactive peptides in Baijiu, fermented grains and distiller's grains - ZENG Yuting, HU Siqi, LIU Hongqin, HUANG Mingquan (Zhongguo niangzao)
In recent years, with the growing emphasis on healthy diets and functional foods, bioactive peptides have garnered significant attention due to their potential nutritional value and physiological functions. At present, although some studies have reported the existence of bioactive peptides in Baijiu, fermented grains (Jiupei) and distiller's grains (Jiuzao), systematic research is still insufficient. In this paper, the preparation, separation, purification and identification methods of peptides were summarized, and the research progress of peptides with antioxidant, anti-inflammatory and antihypertensive activities in Baijiu, Jiupei and Jiuzao was systematically reviewed. Finally, the future research directions of bioactive peptides in Baijiu, Jiupei and Jiuzao were prospected, and corresponding suggestions were put forward. Through in-depth excavation of bioactive peptides in the Baijiu brewing process, it aimed to provide theoretical foundation for the healthy development of the brewing industry, and provide new ideas for the resource comprehensive utilization of brewing by-products and the innovative development of the Baijiu industry.